1990
DOI: 10.1073/pnas.87.9.3279
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of fetal DNA from nucleated erythrocytes in maternal blood.

Abstract: Fetal nucleated cells within maternal blood represent a potential source of fetal genes obtainable by venipuncture. We used monoclonal antibody against the transferrin receptor (TfR) to identify nucleated erythrocytes in the peripheral blood of pregnant women. Candidate fetal cells from 19 pregnancies were isolated by flow sorting at 121/-17 weeks gestation. The DNA in these cells was amplified for a 222-base-pair (bp) sequence present on the short arm of the Y chromosome as proof that the cells were derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
245
0
8

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(257 citation statements)
references
References 33 publications
(22 reference statements)
3
245
0
8
Order By: Relevance
“…For the direct detection of fetal chromosomal and genetic abnormalities from maternal blood, early work focused on the relatively difficult isolation of the rare fetal nucleated cells from maternal blood (3)(4)(5). The discovery of cell-free fetal nucleic acids in maternal plasma in 1997 opened up new possibilities (6,7).…”
Section: Down Syndrome ͉ Solexa Sequencing ͉ Trisomy 21mentioning
confidence: 99%
“…For the direct detection of fetal chromosomal and genetic abnormalities from maternal blood, early work focused on the relatively difficult isolation of the rare fetal nucleated cells from maternal blood (3)(4)(5). The discovery of cell-free fetal nucleic acids in maternal plasma in 1997 opened up new possibilities (6,7).…”
Section: Down Syndrome ͉ Solexa Sequencing ͉ Trisomy 21mentioning
confidence: 99%
“…Applications range from characterization of circulating epithelial cells (CEpCs) in the peripheral blood of cancer patients for disease prognosis and personalized treatment (1)(2)(3)(4)(5)(6)(7); circulating fetal cells in maternal blood for prenatal diagnosis (8)(9)(10); and antigen-specific lymphocytes for immune monitoring (11). The deconvolution of profiling data to extract the relevant biology of rare cells from the mixture of blood leukocytes is challenging, and in most cases impractical (12,13).…”
mentioning
confidence: 99%
“…Bianchi et al, 1990 using CD71 were able to detect the Y chromosomal sequence in 75% of the male-bearing pregnancies in 19 women (1). In 1995, Bianchi et al also showed that CD71 selection using FACS gave the best and consistent results as compared to immunomagnetic beads and MACS (11).…”
Section: Discussionmentioning
confidence: 93%
“…Many methods like Fluorescence Activated Cell Sorting (FACS), Magnetic Activated Cell Sorting (MACS), charge flow separation, immunofluorescent beads, lectins, etc. have been exploited for the isolation of fetal nucleated red blood cells (NRBCs) from maternal peripheral blood (1)(2)(3)(4)(5). Of these, FACS has been the most widely used technique.…”
mentioning
confidence: 99%